2018
DOI: 10.4018/ijthi.2018070102
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Motivation to Comply and Perceived Critical Mass in Smartphones' Adoption

Abstract: The testing of the technology acceptance model over the years has shown that its explanatory power is about 50%; which led researchers to revisit the model in an attempt to gain a better understanding of technology adoption. Some of the studies found social influence to be a key factor, but others have yielded mixed results. This article questions the assumption made in some previous studies that most people would comply with social influence. Using data collected from 210 smartphone users, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The critical mass theory has been used in explaining the adoption and use of technology, especially the ones with network effects, where the value of the technology increases as the number of users increases (Chen et al, 2016). For example, prior IS research has shown that perceived critical mass significantly influences intentions to use, and continuously use, communication technologies such as smartphones (Illia et al, 2018), instant messaging (Gong et al, 2018) and new social networks (Hou et al, 2020). Mobile and online games, although not primarily used for communication, can be considered as an interactive technology with network effects.…”
Section: Perceived Critical Massmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical mass theory has been used in explaining the adoption and use of technology, especially the ones with network effects, where the value of the technology increases as the number of users increases (Chen et al, 2016). For example, prior IS research has shown that perceived critical mass significantly influences intentions to use, and continuously use, communication technologies such as smartphones (Illia et al, 2018), instant messaging (Gong et al, 2018) and new social networks (Hou et al, 2020). Mobile and online games, although not primarily used for communication, can be considered as an interactive technology with network effects.…”
Section: Perceived Critical Massmentioning
confidence: 99%
“…motivation to conform to the important referent's normative beliefs without any change in one's belief or attitudes (Shen et al, 2013). Alternatively, the influence of subjective norms can work indirectly through the mechanisms of internalization (incorporation of the referent's beliefs into one's own belief system) or identification (changing one's belief to establish a self-defining relationship with important referents) (Illia et al, 2018).…”
Section: Subjective Normsmentioning
confidence: 99%
“…Although the actual critical mass threshold is difficult to determine, each potential user may have their own perceived critical mass based on the growing number of adopters of specific technologies in their social circles (Cho, 2011). As previous studies (e.g., Cho, 2011;Illia et al, 2018), in this study the authors used the concept of perceived critical mass to refer to users' perception of whether the critical mass threshold is reached (or how soon it will be).…”
Section: Critical Massmentioning
confidence: 99%
“…According to the diffusion of innovation theory, the adoption and spread of an innovation depend on the critical mass of users defined as the point at which enough individuals have adopted the innovation so that its further rate of adoption becomes self-sustaining (Rogers, 1995). Technology users may have their own perception of whether the critical mass of users has been (or is about to be) reached (Cho, 2011;Illia et al, 2018). If a person's perception that more and more people in their environment or circle of friends are using cryptocurrency exchanges may have a direct impact on their intention to use the service.…”
Section: Figure 1 Caption In Wordsmentioning
confidence: 99%
“…Similarly, the more confident the user is, the more probable their perceived values will guide their adoption behaviour. While the influence of PCM on intention has been analysed by researchers ( George and Sunny, 2021 , Illia et al, 2018 ), its role as a moderator between perceived values and intentions to adopt in the context of mobile payments has not been examined yet. PCM may act as an important moderator in association between perceived values and adoption intentions.…”
Section: Theoretical Supportmentioning
confidence: 99%